The Role Of Socıal And Emotıonal Learnıng (Sel) In Growıng The Socıal And Emotıonal Skılls Of Prımary School Students - Jelita Dwi Septya; Dahlan, Zaini (Jurnal Elementaria Edukasia, 2024)
Good mastery of various skills allows individuals to achieve success in life. This also applies to elementary school-age children. One of the skills that are considered important to master is social and emotional skills. From the results of simple interviews and observations that have been conducted in pre-research at SD Prestige Bilingual School, this school implements the Social and Emotional Learning (SEL) Program as an effort to overcome various social and emotional problems felt by students. From the findings of simple interviews and observations that have been carried out in pre-research, this research was conducted to find out and describe the implementation of Social and Emotional Learning (SEL) in fostering students' social and emotional skills, especially in the implementation of learning. This type of research is qualitative research. The methods used are observation, interview, and document study. This research is located at SD Prestige Bilingual School. From the results of this study it can be concluded that grade 2 students of SD Prestige Bilingual School have good social and emotional skills, although there are still some students who are considered to have to hone their social and emotional skills again. The Social and Emotional Learning (SEL) program has an important role in fostering the social and emotional skills of grade 2 students of Prestige Bilingual School through a series of activities such as SEL learning, classroom goals, meet up, buddy up, community buiders, and SEL week.